Therapeutic Potential of Ramalin Derivatives with Enhanced Stability in the Treatment of Alzheimer’s Disease - Tai Kyoung Kim; Ju-Mi Hong; Jaewon Kim; Kyung Hee Kim; Se Jong Han; Il-Chan Kim; Hyuncheol Oh; Dong-Gyu Jo; Joung Han Yim (Molecules, 2024)
Alzheimer’s disease (AD) remains a significant public health challenge with limited effective treatment options. Ramalin, a compound derived from Antarctic lichens, has shown potential in the treatment of AD because of its strong antioxidant and anti-inflammatory properties. However, its instability and toxicity have hindered the development of Ramalin as a viable therapeutic agent. The primary objective of this study was to synthesize and evaluate novel Ramalin derivatives with enhanced stabilities and reduced toxic profiles, with the aim of retaining or improving their therapeutic potential against AD. The antioxidant, anti-inflammatory, anti-BACE-1, and anti-tau activities of four synthesized Ramalin derivatives (i.e., RA-Hyd-Me, RA-Hyd-Me-Tol, RA-Sali, and RA-Benzo) were evaluated. These derivatives demonstrated significantly improved stabilities compared to the parent compound, with RA-Sali giving the most promising results. More specifically, RA-Sali exhibited a potent BACE-1 inhibitory activity and effectively reduced tau phosphorylation, a critical factor in AD pathology. Despite exhibiting reduced antioxidant activities compared to the parent compound, these derivatives represent a potential multi-targeted approach for AD treatment, marking a significant step forward in the development of stable and effective AD therapeutics.